The Effect of Courses of the Preparation and Training Department to Developing Imagined Fluency According to (VTS) for Some Teachers and Female Teachers of Physical Education in the Karbala Education Directorate - Muntadhar Saheb Mahdi; Ali Hussein Ali; Mazin Jalil Abdulrasool; Wissam Salah Abdul Hussein (Indian Journal of Forensic Medicine & Toxicology, 2021)
The research problem and its importance were dealt with while mentioning the imposition of the researchand its objectives in which the researchers sought to measure imagined fluency with the latest technologicaltechnologies, some physical education teachers and teachers have knowledge of the effect of courses of thepreparation and training department to developing this important mental variable. The researchers also dealtwith the concept and types of fluency, the executive functions of the brain, cognitive flexibility, and othertopics related to the research problem. Then the researchers mentioned the research methodology, its fieldprocedures, the most important tools, devices and tests used, along with a detailed explanation of the ViennaTest System (VTS) abbreviated to (Vienna Test System). To conclude with the research results that werepresented, analyzed and discussed. To come up with conclusions, the most important of which is the positiveimpact of the training courses held by the Preparation and Training Department, recommendations andscientific and practical proposals, most notably the call to establish a contemporary psychological laboratoryin the Iraqi education directorates to measure and develop complex psychological, mental and personalcapabilities. With documentation of Arab and foreign sources and an appendix to a sample for the resultof the (5 point) test, which measures the imagined fluency and cognitive flexibility of the research sample